The Ambient Intelligent Classroom Beyond the Indispensable Educator - Montebello, Matthew (Studies in Computational Intelligence, 2019)
This book explores Ambient Intelligence as applied to the classroom, while especially focusing on the use of personalized education to optimize the learning process. In the years to come, the dynamics of learning spaces in higher education will need to evolve and adapt to a constantly changing digital society, as learners and educators alike attune their learning competences and teaching skills. Ambient Intelligence is another way that Artificial Intelligence is being utilized in a plethora of real-world situations, amongst which classrooms and other learning spaces offer fitting settings and ideal environments for employing this assistive technology. The book presents a complete and novel approach to deploying the Ambient Intelligent Classroom, based on three interrelated aspects - the Social, the Technological and the Educational, - in order to provide a rich three-dimensional learning environment. This book is intended for education technologists and AI researchers, as well as for those tech-savvy readers interested in applying technology to the future of learning spaces. Educators in particular will find valuable insights and guidelines on how to shape the evolution of their own classroom.